INVESTIGATION OF THE CONTRIBUTION OF GENETIC VARIANTS ON THE DEVELOPMENT OF OBESITY AND METABOLIC COMPLICATIONS IN A MULTI-ETHNIC CONTEXT - Stryjecki, Carolina (My University, 2019)
Obesity is a complex, multifactorial disease associated with several metabolic complications including type 2 diabetes (T2D) and cardiovascular disease. Obesity is also characterized by a state of chronic low-grade inflammation due to dysregulated adipokine secretion and macrophage infiltration, which is believed to be the pathophysiological link between obesity and other metabolic complications. It is currently unclear if inflammation is a cause of obesity and metabolic complications, or merely a consequence of it. Moreover, some ethnic groups are disproportionately affected by obesity and its metabolic complications, suggesting underlying genetic differences in the susceptibility to obesity. This thesis aims to (1) to provide a comprehensive discussion of the ethnic differences in the genetic architecture of obesity, including a meta-analysis of heritability estimates of body mass index (BMI) from various ethnic groups, (2) examine the effects of the PPARγ Pro12Ala polymorphism on T2D-related traits, (3) investigate the contribution of genetic variants in inflammation-related genes on metabolic traits, and (4) determine the effects of genetic variation in the insulin sensitizing adipokine adiponectin and cardio-metabolic traits, aims (2), (3) and (4) being investigated in a high-risk population of Mexican children. The major findings are (1) there is no difference between heritability estimates for BMI among African, admixed American and Asian populations, relative to Europeans, and in Mexican children: (2) circulating lipids can interact with PPARγ Pro12Ala to modulate markers of insulin resistance, (3) there is no association between inflammation-related genes and metabolic traits, and (4) circulating adiponectin concentration is strongly associated with metabolic traits. Together this thesis provides insight into the biological mechanisms involved in obesity and its metabolic complications. With a better understanding of the molecular mechanisms involved, more effective prediction of high-risk individuals, preventions and treatments and can be developed.